How the Workforce of the Future Applies a Circular Economy Through Advanced Modular Building Technology - Minunno, Roberto; Syminton, Lee (2021)
INTRODUCTION: The construction and demolition sectors produce about 40% of waste by mass worldwide. The circular economy framework posits that waste minimisation can be achieved by turning waste into new resources. The circular economy has gained substantial traction among practitioners and academics alike, and it is has been applied in many industry sectors, from the fashion industry to reusable water bottles. However, when it comes to buildings, three main challenges arise. First, buildings are built as monoliths, which cannot be easily disassembled and reused. Second, buildings are built to satisfy architectural and people’s needs, which often means that their components are bespoke and all different. Third, a closed-loop of second-life building components does not exist yet. To overcome these challenges, we trained the future workforce on the disassemblability and reusability of modular buildings. METHODS: The Legacy Living Lab was built embedding into a new construction reused components. Further, these components were designed to be disassemblable and allow the building to be easily moved to another site – thus extending its life cycle. Once the Legacy Living Lab was completed, however, one of its primary functions was to educate the future workforce on the circular economy of buildings. To pursue this objective, Curtin’s academics integrate learnings from the Lab into their lectures so that the students can complement their classes with site visits, touching with their hands the final product. Curtin’s architecture students versed nine Australian Universities in the Fleetwood Challenge Cup during the last academic year. The Cup is a yearly competition that sees groups of Architecture students proposing modular buildings ideas to deliver circular economy solutions towards a sustainable future. RESULTS: We present two sets of results. The first set regards the environmental performances of the Legacy Living Lab, and the second regards the results of the Fleetwood Challenge Cup. Applying the circular economy framework to modular buildings allowed a whopping saving of 20 tons of concrete, 18 tons of steel from the waste stream, and 88% of greenhouse gas emissions. Regarding the Cup, Curtin’s workforce of the future scored the first, third and fourth positions, which is a remarkable result (the second position was awarded to a group from Deakin University). CONCLUSIONS: In conclusion, the Architects of the future should be equipped with applied and theoretical knowledge on the circular economy concept. It allows a substantial environmental benefit and can easily be integrated with Architectural qualities.